Peran dan Gagasan Susilo Bambang Yudhoyono dalam Resolusi Konflik Aceh - Supriadi Supriadi; Nirzalin Nirzalin; Mursyidin Mursyidin (Jurnal Sosiologi Agama Indonesia (JSAI), 2022)
The Aceh peace achieved in 2005 has become an example for the international community in resolving conflicts using a dialogue approach. Of course, it cannot be separated from the role and ideas of Susilo Bambang Yudhoyono as the president of the Republic of Indonesia at that time. This article aims to describe SBY's role and ideas in Aceh's conflict resolution context. The data in this study are sourced from relevant literature studies and analyzed with a qualitative approach. This study shows that several basic things are important points in the context of SBY's role and ideas in pursuing peace in Aceh. First, peace efforts are based on sincerity and political commitment to end the conflict. Second, the ability to see difficulties during a tsunami becomes an opportunity for peace. Third, the choice of a non-militaristic approach and relying on dialogue. Fourth, courage in taking risks and realizing measurable policies in pursuing peace in Aceh. Apart from that, the commitment to peace from the government and GAM is an important point in the realization of peace in Aceh because the commitment to peace by complying with the points of the agreement has been agreed upon and makes peace continue. Abstrak Perdamaian Aceh yang berhasil diraih pada tahun 2005 telah menjadi contoh bagi dunia internasional tentang bagaimana menyelesaikan konflik bersenjata dengan pendekatan dialog. Hal ini tentunya tidak terlepas dari peran dan gagasan Susilo Bambang Yudhoyono yang kala itu menjadi presiden Republik Indonesia. Dengan menggunakan pendekatan kualitatif, artikel ini bertujuan untuk mendeskripsikan lebih lanjut tentang peran dan gagasan SBY dalam konteks resolusi konflik di Aceh Data dalam penelitian ini bersumber dari kajian-kajian literatur yang relevan. Kajian ini menunjukkan bahwa terdapat beberapa hal mendasar yang menjadi poin penting dalam konteks peran dan gagasan SBY dalam mengupayakan perdamaian Aceh. Pertama, upaya perdamaian yang di dasarkan pada kesungguhan dan komitmen politik untuk benar-benar mengakhiri konflik. Kedua, kemampuan dalam melihat kesulitan di tengah tsunami menjadi peluang untuk berdamai. Ketiga, pilihan pendekatan non militeristik dan bertumpu pada dialog. Keempat, keberanian dalam mengambil risiko dan realisasi kebijakan yang terukur dalam mengupayakan perdamaian di Aceh. Terlepas pada itu, komitmen perdamaian dari pemerintah dan GAM menjadi poin penting dari realisasi perdamaian Aceh, karena komitmen damai dengan cara mematuhi poin-poin perjanjian yang telah disepakati membuat perdamaian dapat terus bertahan.